الفقه : دراسة فكرية إسلامية - Muh Barid Nizarudin Wajdi (STAI Miftahul Ula Nganjuk, 2018)
Scholars argue that in the Islamic law there are all laws that govern all human behavior, both word and deed. These laws are sometimes stated explicitly and strictly and sometimes only in the form of arguments and rules in general. To understand Islamic law in the form of the first one is not necessary ijtihad, but simply taken and practiced as it is, because it is clearly and explicitly called by Allah. Islamic law in this form is called pure revelation. As for the knowledge of Islamic law in the second form, it is necessary for the sincere efforts of the mujtahids to dig into the law contained in the nash through careful study and understanding; The whole law set forth in this manner is called fiqih.